Corrective treatment of ectopic eruption of permanent first molars : case report = Tratamiento correctivo de erupción ectópica de primeros molares permanentes : reporte de casos - Gutiérrez Marín, Natalia 1975-
Ectopic eruption of a tooth is the process in which a tooth emerges in an abnormal position. The first permanent molar is the tooth that most frequently presents ectopic eruption, mostly because it is retained below the distal contour of the second temporary molar. The ectopic eruption may be reversible or irreversible, the latter of which requires corrective treatment to achieve correct eruption of the permanent molar in the arch. Treatments can be minimally invasive, such as the use of interproximal wedging, or more invasive orthodontic devices, such as brass wire, k-loops, Halterman devices, or wedging springs. The aim of this case report is to present two clinical cases where the ectopic eruption of permanent first molars is corrected using elastic separators. Conclusion:The elastic separators could be used successfully in cases of moderate or severe ectopic eruptions, not only in mild cases, as reported in most of the literature. The use of this technique does not require great cooperation from the patient, and it is low in cost.